Potentiation of GABAergic synaptic transmission by diazepam acutely increases resting beat-to-beat blood pressure variability in young adults - Teixeira, André L.; Nardone, Massimo; Samora, Milena; Fernandes, Igor A.; Ramos, Plinio S.; Sabino-Carvalho, Jeann L.; Ricardo, Djalma R.; Millar, Philip J.; Vianna, Lauro C. (American journal of physiology. Regulatory, integrative and comparative physiology, 2022)
Resting beat-to-beat blood pressure variability is a powerful predictor of cardiovascular events and end-organ damage. However, its underlying mechanisms remain unknown. Herein, we tested the hypothesis that a potentiation of GABAergic synaptic transmission by diazepam would acutely increase resting beat-to-beat blood pressure variability. In 40 (17 females) young, normotensive subjects, resting beat-to-beat blood pressure (finger photoplethysmography) was continuously measured for 5–10 min, 60 min after the oral administration of either diazepam (10 mg) or placebo. The experiments were conducted in a randomized, double-blinded, and placebo-controlled design. Stroke volume was estimated from the blood pressure waveform (ModelFlow) permitting the calculation of cardiac output and total peripheral resistance. Direct recordings of muscle sympathetic nerve activity (MSNA, microneurography) were obtained in a subset of subjects ( n = 13), and spontaneous cardiac and sympathetic baroreflex sensitivity were calculated. Compared with placebo, diazepam significantly increased the standard deviation of systolic blood pressure (4.7 ± 1.4 vs. 5.7 ± 1.5 mmHg, P = 0.001), diastolic blood pressure (3.8 ± 1.2 vs. 4.5 ± 1.2 mmHg, P = 0.007), and mean blood pressure (3.8 ± 1.1 vs. 4.5 ± 1.1 mmHg, P = 0.002), as well as cardiac output (469 ± 149 vs. 626 ± 259 mL/min, P < 0.001) and total peripheral resistance (1.0 ± 0.3 vs. 1.4 ± 0.6 mmHg/L/min, P < 0.001). Similar results were found using different indices of variability. Furthermore, diazepam reduced MSNA (placebo: 22 ± 6 vs. diazepam: 18 ± 8 bursts/min, P = 0.025) without affecting the arterial baroreflex control of heart rate (placebo: 18.6 ± 6.7 vs. diazepam: 18.8 ± 7.0 ms/mmHg, P = 0.87) and MSNA (placebo: −3.6 ± 1.2 vs. diazepam: −3.4 ± 1.5 bursts/100 Hb/mmHg, P = 0.55). Importantly, these findings were not impacted by biological sex. We conclude that GABA A receptors modulate resting beat-to-beat blood pressure variability in young adults.